2019
DOI: 10.1038/s41416-019-0410-0
|View full text |Cite
|
Sign up to set email alerts
|

Phase III randomised trial comparing 6 vs. 12-month of capecitabine as adjuvant chemotherapy for patients with stage III colon cancer: final results of the JFMC37-0801 study

Abstract: Background Up to 6-months oxaliplatin-containing regimen is now widely accepted as a standard adjuvant chemotherapy for stage III colorectal cancer (CRC). However, oral fluoropyrimidine monotherapy is used for some part of patients, especially in Asian countries including Japan, and its optimal duration is yet to be fully investigated. Methods A total of 1306 patients with curatively-resected stage III CRC were randomly assigned to receive capecitabine (2500 mg/m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“… 1 , 2 , 3 In Japan, oral fluoropyrimidines, such as capecitabine, tegafur-uracil and LV (UFT/LV), and S-1, are preferred because they have demonstrated favorable outcomes in patients with stage III colon cancer in Japanese randomized trials, and their treatment is convenient and associated with only mild toxicity. 4 , 5 , 6 , 7 However, stage III includes patient subgroups showing very poor outcomes, such as the N2 disease. 4 , 7 According to the Japanese Classification of Colorectal Carcinoma (7th edition), the main lymph nodes are defined as lymph nodes around the origin of the feeding arteries (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 , 2 , 3 In Japan, oral fluoropyrimidines, such as capecitabine, tegafur-uracil and LV (UFT/LV), and S-1, are preferred because they have demonstrated favorable outcomes in patients with stage III colon cancer in Japanese randomized trials, and their treatment is convenient and associated with only mild toxicity. 4 , 5 , 6 , 7 However, stage III includes patient subgroups showing very poor outcomes, such as the N2 disease. 4 , 7 According to the Japanese Classification of Colorectal Carcinoma (7th edition), the main lymph nodes are defined as lymph nodes around the origin of the feeding arteries (i.e.…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 , 6 , 7 However, stage III includes patient subgroups showing very poor outcomes, such as the N2 disease. 4 , 7 According to the Japanese Classification of Colorectal Carcinoma (7th edition), the main lymph nodes are defined as lymph nodes around the origin of the feeding arteries (i.e. the ileocolic, right colic, middle colic, or inferior mesenteric artery; Supplementary Figure S1 , available at https://doi.org/10.1016/j.esmoop.2021.100077 ).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In Japan, oral fluoropyrimidines such as capecitabine, tegafur-uracil and leucovorin (UFT/LV), and S-1 have been preferred because oral fluoropyrimidines alone demonstrated favorable outcomes in patients with stage III colon cancer, most of whom underwent D3 lymph node dissection (3-year disease-free survival [DFS] rate, 70.0%-82.0%), in Japanese randomized trials, and their treatment is convenient and associated with mild toxicities. [4][5][6][7] However, stage III disease includes subgroups of patients with very poor outcomes. In the ACTS-CC trial, the 3-year DFS rate in patients with stage IIIA, IIIB, and IIIC disease who received UFT/LV were 87.9%, 74.2%, and 46.4%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…4 In the JFMC37-0801 study, the 3-year DFS rate in patients who received capecitabine showed a similar trend. 7 There remains room for improvement in the outcomes of patients with such high-risk stage III disease. More aggressive regimens including oxaliplatin are expected to be effective.…”
Section: Introductionmentioning
confidence: 99%
“…Capecitabine (an oral prodrug of 5-fluorouracil) and 5-fluorouracil have long been the backbone of chemotherapy for stages II–III colon cancer in the adjuvant setting [ 13 ]. The duration of treatment has been proven most efficient when given for six months [ 14 ]. Haematological treatment requirements are neutrophils ≥1.5 × 10 9 /L and thrombocytes ≥100 × 10 9 /L.…”
Section: Introductionmentioning
confidence: 99%